Analisis Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Keputusan Pembelian Vocher Paket Data Internet Rt/Rw Net Rancapaku - Sidiq, Ahmad Zamakhsyari; Haerumansyah (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
RT/RW Net Desa Rancapaku is a company engaged in internet services. This research aims to determine the factors that influence consumers towards purchasing RT/RW Net Rancapaku internet data voucher. This research is in accordance with the proposed hypothesis, namely that there is a significant and positive relationship between the price of internet data package cards and product quality and the influence of purchasing decisions. The method used in this research uses linear regression analysis. The results of this research show the result Then the product quality is 0.001 < 0.01 and the calculated t value is 3.817 > from t table 2.000, so it can be concluded that H2 is accepted and the constant is 15.183, meaning that the consistent value of the participation variable is 15.183. The internet data package regression coefficient (X1) is 0.535 and quality 0.470 (X2) states that for every 1% increase in the value of X1 and X2, the participation value increases by 0.535 for X1 and X2 0.470. The regression coefficient is positive, so it can be said that the price of internet data packages and product quality have a positive influence on purchasing decisions for internet data vouchers.